Examination of Objects’ Marking in Complex Forensic Expertise of Alcohol-Containing Liquids - I. L. Kazantseva; V. V. Egorova (Теория и практика судебной экспертизы, 2020)
The stage of object visual inspection is essential in the expertise of alcohol-containing liquids in original (or simulating original) packaging with undisturbed cork, integrity including the examination of a consumer container’s marking. The information obtained by experts at this stage allows them to derive a more comprehensive description of the object and to determine its additional features, which helps to reach conclusions about the method of product manufacturing. Generalized requirements of current Russian regulatory documents (Technical Regulation of the Customs Union TR TS 021/2011, Federal Law No. 171-FL dated November 22, 1995, state standards) for the composition and content of consumer information for vodka as well as examples from the expert practice of examining the markings of alcohol-containing liquids, declared as “vodka” are presented in the article.